Fibrinogen-binding proteins of Gram-positive bacteria - Rivera, Jose; Vannakambadi, Ganesh; Höök, Magnus; Speziale, Pietro (Thrombosis and Haemostasis, 2007)
Fibrinogen (Fg), the major clotting protein in blood plasma, plays key roles in blood coagulation and thrombosis. In addition, this 340 kD glycoprotein is a stress inducible protein; its synthesis is dramatically upregulated during inflammation or under exposure to stress such systemic infections.This regulation of Fg expression indicates that Fg also participates in the host defense system against infections. In fact, a number of reported studies have demonstrated the involvement of both the intrinsic and extrinsic pathways of coagulation; the thrombotic and the fibrinolytic systems in the pathophysiology of infectious diseases. It is, therefore, perhaps not surprising that many pathogenic bacteria can interact with Fg and manipulate its biology.This review focuses on the major Fg-binding proteins (Fgbps) from Gram-positive bacteria with an emphasis on those that are known to have an effect on coagulation and thrombosis
Keywords: Bacterial infection; infectious diseases; bacteria; fibrinogen / fibrin; protein function / activity